An Analysis of Grammatical Errors Made by Students in Writing Descriptive Text - Ihsan Nazir; Arifin Syamaun; Nira Erdiana (Universitas Syiah Kuala, 2019)
This study is aimed at analyzing the grammatical errors and causes of them in writing descriptive text. The study describes the errors that the students made in writing descriptive text based on surface strategy taxonomy (omission, addition, misformation, and misordering). The study used descriptive qualitative method. The population of this research was the second year students of SMAN 1 Mesjid Raya. The class Xl-MIPA 2 was chosen as the sample based on purposive sampling technique. The number of sample was 27 students. The instrument was test where students were asked to write a descriptive text that consists of 30 to70 words in paragraph based on the picture given. The test was conducted on September 19th 2017 taking place at SMAN 1 Mesjid Raya. The result shows there were 75 items of error in the students’ writing. The researcher found that 44% errors of misformation, 25.33% errors of disordering, 20% errors of omission, and 10.67% errors of addition. Based on those findings, it can be concluded that many of the second year students at SMAN 1 Mesjid Raya made grammatical errors in writing descriptive text. They made errors in misformation, disordering, omission, and addition.The researcher found the highest frequency of errors was misformation and the lowest frequency was addition. The researcher also found the cause of errors 44% of first language, 31% of carelessness and 25% of translation. They made the cause of errors appearing in first language, involve carelessness and translation. Therefore, this study was suggested to give an expository about writing a descriptive text in a proper ways of teaching for teachers. For students, it is expected the students can find their entrance for having a good hand in writing descriptive text.